Rape: a South African nightmare - Gqola, Pumla Dineo (MFBooks Joburg, 2018)
"South Africa has a complex relationship with rape. Pumla Dineo Gqola unpacks this relationship by paying attention to patterns and trends of rape, asking what we can learn from famous cases and why South Africa is losing the battle against rape. Gqola looks at the 2006 rape trial of Jacob Zuma and what transpired in the trial itself, as well as trying to make sense of public responses to it. She interrogates feminist responses to the Anene Booysen case, amongst other high profile cases of gender-based violence. " -- Publisher's description: http://www.jacana.co.za/book-categories/current-affairs-a-history/rape-a-south-african-nightmare-detail